Estudo de polimorfismos em genes relacionados ao metabolismo do ácido fólico e sua associação com o desenvolvimento de fendas orais não-sindrômicas - Bezerra, João Felipe (2010)
The congenital facial clefts are characterized by incomplete formation of the structures that separate the oral and nasal cavity. It is known that several environmental and genetic factors are involved in its development, among these, polymorphisms associated with folic acid metabolism have been investigated. In this sense, the objective was to observe the frequency of polymorphisms C677T and A1298C methylenetetrahydrofolate reductase gene (MTHFR), methionine synthase A2756G of (MTR), A66G of methionine synthase reductase (MTRR) A80G and the reduced folate carrier (RFC1) in patients with non-syndromic oral clefts, trying to match them with their development. Methods: We studied 140 patients with non-syndromic oral clefts and their mothers and 175 control subjects with their mothers, who underwent a questionnaire to obtain family information. Were collecting blood for DNA extraction from patients and their mothers to identify the genotypes of both by PCRRFLP, in addition to carrying out the determination of glucose, AST, ALT and serum creatinine, folic acid and vitamin B12 Serum and plasma homocysteine, and the hemogram. Results: Most patients have cleft lip and palate (55.8%), followed by isolated cleft palate (24.2%) and cleft lip (20%). Regarding gender, 62% of patients were male and 48% female and, after subdivision of the type of screwdriver according to sex was found a prevalence of males in the cracks of the type lip and palate (69 %) and lip (69.2%) and in the case of cleft palate was a female predominance (59%). The average concentration of serum folate in the group of mothers of cleft patients was significantly lower (13.8 ± 2.4 ng / mL) compared with the group of mothers of control subjects (18.8 ± 3.4 ng / mL) This was also observed for the group of cleft children as compared to controls, the dosage of folic acid had a significant difference with values of 15.6 ± 0.6 (ng / mL) and 17.9 ± 0.6 (ng / mL), respectively. For the biochemical measurements of glucose, AST, ALT and creatinine were not statistically different, nor was observed for haematological parameters performed. In assessing the frequency of polymorphisms C677T and A1298C MTHFR, A2756G MTR, MTRR A66G and A80G of the RFC1 there was no statistically significant difference in genotype distribution between cases and controls both for mothers and in the cleft. Conclusion: Although not observed association of polymorphisms with the development of cracks, the decrease in serum folate in the group of cleft patients and their mothers may reflect a disturbance in the metabolism of this metabolite, necessitating further studies such as studies methylation and expression to further elucidate the involvement of folate in the development of oral clefts